An Analysis of Passengers’ Shopping Behaviour in the Departure Lounge: The Importance of Non-aeronautical Income for Airport Operations - Zuendel, Anna (2012)
This study deals with airport shopping behaviour of travellers in a departure lounge with the major aim of providing a basis for future airport marketing activities. Due to the increasing number of privatisations of airports profit maximization has been gaining in importance. This can be more easily achieved by concentrating on nonaeronautical income than aeronautical income, as these are more manageable by an airport itself. One main source of income is made up of airport retailing. Customers need to get a business’ full attention. Airport managers thus need to concentrate on their passengers in order to improve non-aeronautical revenues. Understanding their needs and desires helps to effectively develop marketing strategies, which help to increase commercial income. The dissertation focuses on main influences on airport shopping behaviour including purchase involvement levels, impulse buying as the main purchasing behaviour at an airport as well as tourist behaviour at an airport. A review of the literature on airport development and airport shopping behaviour will be supported by data gained from primary research in terms of intercept surveys in the departure lounge of Birmingham Airport. The findings revealed that most purchases made at the airport were of a low involvement nature. Furthermore, most purchases were also made due to impulse buying including planned impulse purchases. It is however, debatable in how far impulse buying behaviour and involvement levels relate to each other. A special tourist behaviour at an airport could not be exposed. Nevertheless, it is still an important topic that should be further examined as most of the leisure travellers were already in a holiday mood before they arrived at their destination. If tourist behaviour has an influence on airport shopping airport marketing managers should focus on making their holidays already start at the airport. Another issue to elaborate on is the effective use of the tool of sales promotion in an airport in order to reach consumers and increase non-aeronautical income.